The buckling strength of plexiglass protective shield under static water pressure. (May 2019) - Zhang, Yue-lin; Jin, Jian; Hou, Hai-liang; Liu, Shu-yong; Wei, Xiu-lei
Abstract: The protective shield of PMT (photon multiplier tubes) is a typical spherical-cylindrical thin-walled shell structure which works in the environment of deep water pressure with the material of plexiglass and character of low Young's Modulus. Therefore, it is significant to analyze the stability of the structure. The validity of eigenvalue buckling prediction and arc length method was verified by classic buckling theory of rotation shell firstly. Then the stability of plexiglass shield was researched by these two methods and a general calculation formula of shallow shell was fitted. The results show that the critical stress of plexiglass shield decreases with the reduction of section roundness; if the height of cylindrical shell is less than 0.3 R, there is no influence on sphere-cylindrical shell structure, but when the height is more than 0.3 R, the structure stability decreases with the increasing of cylindrical shell height. If the influence of exhaust orifice is considered, the geometry of shell is the main factor for the stability of shell when the orifice radius is less than 0.3 times of orifice spacing. Otherwise, orifice is the main factor for the stability of shell. There is a significant influence of initial imperfection on the critical stress of the protective shield and the critical stress decreases with the increasing of initial deformation. The research of this paper can provide useful guidance for the design of PMT plexiglass shield. Highlights: A simplified stability calculation formula of shallow shell under uniformly distributed pressure is fitted. The critical stress of plexiglass shield decreases with the reduction of section roundness. If the influence of exhaust orifice is considered, the geometry of shell is the main factor for the stability of shell, when the orifice radius is less than 0.3 times of orifice spacing. Otherwise, orifice is the main factor. If initial deformation is considered, there is a little reduction of shield critical stress, and the critical stress decreases with the increasing of initial deformation factor.